The last dynasty : ancient Egypt from Alexander the Great to Cleopatra - Wilkinson, Toby, 1969- (W. W. Norton & Company, 2025)
"A definitive and thrilling new account of the last great dynasty of ancient Egypt, from Alexander the Great to Cleopatra. When Alexander the Great arrived in Egypt, he overthrew the hated Persian overlords and was welcomed as a saviour. He repaid them by showing due reverence to their long-held traditions. After his death, as the Greek empire broke up and his closest advisers squabbled over the spoils, a Macedonian general named Ptolemy seized the Egyptian throne, ushering in a new dynasty that would last for 300 years. What followed was as dramatic and compelling as any period in Egyptian history. The unique blend of Greek and Egyptian cultures led to an unprecedented flowering of learning, as the new city of Alexandria became home to the Great Library, the largest in the ancient world, that attracted the brightest minds. Wars, incest, double-dealing, foreign empires and huge wealth all followed, but the rise of the Roman empire would eventually bring the Ptolemaic era crashing to a close. Helped by the latest archaeological discoveries and using original papyrus documents, Toby Wilkinson uncovers a story that can only now be fully told. From courtly life to the role of women, from international trade to the tensions between native Egyptians and incoming Greeks, all aspects of life are here. Filled with surprising insights, vivid descriptions and larger-than-life characters, and written in the author's compelling narrative style, The Last Dynasty will appeal to all lovers of history, archaeology, art and culture"--Publisher's description.